Передовий інструментарій ресурсно-бюджетного та організаційно-технологічного моделювання будівельного виробництва - Горбач, М. В. (Ways to Improve Construction Efficiency, 2014)
The complex organizational and technological models of management training building projects on the basis of development, providing the customer the ability to predict the occurrence of force majeure events and consider their implications for changing key parameters adopted variant preparation of construction.